Implementasi Manajemen Resiko Syariah Dalam Koperasi Syariah - Wahyu Hidayat (STAI Asy-Syukriyyah, 2019)
The existence of sharia risk management is to guarantee the existence of a Sharia Cooperative in the long run. With sharia risk management, it is expected to be able to provide guidance for the Sharia / Baitul Maal Wa Tamwil Cooperative in implementing sharia risk management in its business operations, especially for cooperatives that are engaged in sharia financial services or known as Sharia Credit and Financing Cooperatives (KSPPS) . In any business activity it has the potential to risk. Risk is defined as uncertainty caused by changes. There are various kinds of risks in the operations of sharia cooperatives such as financing risk, liquidity risk, margin, organization, solvency, operational, capital, legal risk and compliance with sharia principles. Risk management is done so that the risk can be minimized to a minimum, so that plans and targets that have been planned can be realized so as to produce benefit. In the implementation of risk management in Islamic cooperatives can combine SWOT analysis, prudential concept with 5C and Maqosid Syariah. In principle, every business activity has a risk, but we can minimize the risk to the lowest point if we do it in the right way and according to sharia.